Brand Awareness, Brand Loyalty, Perceived Quality, Brand Association Brand Preference dan Purchase Intention - Ngurah Bagus Angga Primanda Kusuma; I Putu Miartana (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe goal of this research is to analyse the influence of brand awareness, brand loyalty, perceived quality, yet brand association to brand preference and Purchase Intention. The design of this research is quantitative, ie the relationship of causality between variables. The study was conducted at Ungasan Clifftop Resort. Data collection techniques used questionnaires to 108 consumers Ungasan Clifftop Resort. Data were analyzed by data analysis technique Structure Equation Modeling with AMOS program. The result of research shows 1) the influence of latent variable of brand awareness to latent variable of brand preference is positive, 2) latent variable of brand loyalty to latent variable of brand preference is positive, 3) latnt variable of perceived quality to ltent brand preference variable is significantly positive, 4) the affect of latent brand association variable to latent variable of brand preference is positive, 5) influence of latent variable of brand awareness to latent variable purchase itention is positive, 6) influence of latent variable of brand loyalty to latent variable purchase itention is positive the latent variable perceived quality to latent variable purchase itention is positive, latent attribute brand association (x4) to latent variable purchase itention is positive, 9) influence of latent brand preference variable to latent variable purchase itention is positive.